Emerging role of Raoultella ornithinolytica in human infections: a series of cases and review of the literature. (April 2016) - Seng, Piseth; Boushab, Boushab Mohamed; Romain, Fanny; Gouriet, Frédérique; Bruder, Nicolas; Martin, Claude; Paganelli, Franck; Bernit, Emmanuelle; Treut, Yves Patrice Le; Thomas, Pascal; Papazian, Laurent; Raoult, Didier; et al.
Graphical abstract: Highlights: Raoultella ornithinolytica pneumonia and pleural effusion were observed in 24% of cases. Cases of osteomyelitis, meningitis, and cerebral abscess are reported for the first time. The proportion of R. ornithinolytica isolates resistant to antibiotics was relatively high. The mortality rate related to infection was 5% of cases. R. ornithinolytica is underreported and particularly associated with invasive procedures. Summary: Background: Raoultella ornithinolytica is known to inhabit aquatic environments. The clinical features and outcomes of human infections caused by R. ornithinolytica have been reported for only a limited number of cases. Methods: A retrospective study of cases of infection caused by R. ornithinolytica managed at four university hospital centres during the period before and after the introduction of matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) was performed. The aim was to describe the clinical and microbiological characteristics, treatments, and outcomes. Results: Among 187 R. ornithinolytica isolates identified for which clinical information was available, 71 were considered colonizers and 116 were pathogenic. A total of 112 cases of R. ornithinolytica infection were identified. Urinary tract infections, gastrointestinal infections, wound and skin infections, and bacteraemia were observed in 36%, 14%, 13%, and 5% of cases, respectively. Associated infections that have been poorly reported, such as respiratory infections, i.e. pneumonia and pleural effusion, were observed in 24% of cases. Additional diseases reported here for the first time included osteomyelitis, meningitis, cerebral abscess, mediastinitis, pericarditis, conjunctivitis, and otitis. The proportion of R. ornithinolytica isolates resistant to antibiotics was found to be relatively high: 4% of isolates were resistant to ceftriaxone, 6% to quinolones, and 13% to co-trimoxazole. The mortality rate related to infection was 5%. Conclusions: R. ornithinolytica is an underreported, emerging hospital-acquired infection and is particularly associated with invasive procedures. R. ornithinolytica should never be considered simply a saprophytic bacterium that occasionally contaminates bronchial lavage or other deep respiratory samples or surgical sites. Physicians should be aware of the high rates of antimicrobial resistance of R. ornithinolytica isolates so that immediate broad-spectrum antibiotic treatment can be established before accurate microbiological results are obtained.